Clinical Characteristics of Severe COVID-19 Patients Admitted to an Intensive Care Unit in Lombardy During the Italian Pandemic - Briguglio, Matteo; Crespi, Tiziano; Pino, Fabio; Mazzocchi, Marco; Porta, Mauro; De Vecchi, Elena; Banfi, Giuseppe; Perazzo, Paolo (Frontiers in Medicine, 2021)
Italy was one of the worst affected European countries during the SARS-CoV-2 pandemic. More than 50% of Italian cases occurred in the northern region of Lombardy, where the saturation of health services between March and April 2020 forced hospitals to allocate patients according to available resources. Eighteen severe COVID-19 patients were admitted to our hospital needing intensive support. Given the disease fatality, we investigated patients’ characteristics to identify mortality predictors. We counted seven deaths from multiple organ failure, two from septic shock, and two from collapsed lungs. The maximum case fatality was observed in patients who contracted SARS-CoV-2 in hospitals. The fatal outcome was associated with the following baseline characteristics: polymorbidity (OR 2.519, p = 0.048), low body mass index (OR 2.288, p = 0.031), low hemoglobin (OR 3.012, p = 0.046) and antithrombin III (OR 1.172, p = 0.048), along with a worsening of PaO2/FiO2 ratio in the first 72 hours after admission (OR 1.067, p = 0.031). The occurrence of co-infections during hospitalization was associated with a longer need for intensive care (B 4.511, p = 0.001). More information is needed to inform intensive care for patients with severe COVID-19, but our findings would certainly contribute to shed some light on this unpredictable and multifaceted disease.